Project-based Learning for the Development of Research Competence in Basic Education Students (Docentes 2.0 Journal, 2024)
Mastering research skills is essential for forming other skills in academic processes, but they will also be fundamental in people's professional development. The research aimed to determine the influence of project-based learning on the development of investigative competence in first-grade secondary school students in the Peruvian context. The research has been conducted within the positivist paradigm, quantitative approach, and applied type, implementing a longitudinal quasi-experimental design. The population was first-grade secondary school students, with an intentional sample of 71, of which 35 participated as the experimental group and 36 as the control group. The observation sheet was used to collect data for the independent variable, and a questionnaire of questions for the dependent variable. Reliability was determined through Cronbach's Alpha. The data were processed with the SPSS program, using tables to describe the variables and the Man Whitney U test to test the hypothesis. The results in the pretest for both groups showed that the students were at the beginning, while, in the post-test, for the experimental group, the level of competence increased to 77.1%. This result was verified through the Mann-Whitney U test with a Z value=-7.259 and significance level p-value=0.000. It is concluded that project-based learning significantly influences the development of research competence in first-grade secondary school students.
Keywords: Project-based learning; investigative competence; cognitive; procedural; communicative